2014
DOI: 10.1007/s00104-014-2852-5
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginale Cholezystektomie

Abstract: The results did not show superiority of TVC over CLC with regards to postoperative pain. With no differences in postoperative pain and high patient satisfaction, TVC can be recommended to future patients as an alternative method. For confirmation of this evaluation of TVC further randomized trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Over 93% of our female patients were satisfied with the surgical result. There are also high satisfaction ratings in the literature regarding the transvaginal cholecystectomy [13,14]. For example, Linke et al reported a general satisfaction rate of 95.5% [15], which is comparable with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Over 93% of our female patients were satisfied with the surgical result. There are also high satisfaction ratings in the literature regarding the transvaginal cholecystectomy [13,14]. For example, Linke et al reported a general satisfaction rate of 95.5% [15], which is comparable with our results.…”
Section: Discussionsupporting
confidence: 90%